Cultural heritage and iconic elements for history education: a study with primary education prospective teachers in Spain - Diego Miguel-Revilla; Esther López-Torres; Jorge Ortuño-Molina; Sebastián Molina-Puche (Humanities & Social Sciences Communications)
Abstract Cultural heritage, both in its tangible and intangible dimensions, is a very influential element that is closely connected with history education and with identity-building. The present study seeks to identify the cultural iconic elements that pre-service social science educators associate with the history of Spain, as well as their sources of information. A semi-structured questionnaire was administered to 668 prospective teachers of four Spanish regions who were enroled in bachelor’s degrees in primary education. Participants were asked to spontaneously name the four iconic elements (monuments, works of art, places, festivities, traditions, etc.) that they considered the most representative of Spanish history. Finally, they were asked about the sources of information that they used in order to gain knowledge about these elements. Results revealed that some iconic elements connected with cultural and historical heritage were predominant in the collective consciousness of trainee teachers. Furthermore, while the influence of school was noticeable, an even stronger influence of the social context and families was detected in their selection. Results suggest that the educational potential of cultural icons that are familiar to learners should be used in initial teacher training and history education. This would allow prospective teachers to promote engagement and develop an understanding of historical multiperspectivity among their students, fostering critical citizenship.